CURRENT VIEWS IN THE DIAGNOSIS AND TREATMENT OF PATIENTS WITH DIABETIC FOOT SYNDROME (Academia Science Repository, 2023)
The diabetes mellitus is one of the most serious medico-social problems of our time relating to the priority directions of national health systems of all countries. One of dangerous chronic complications of DM is the syndrome of diabetic foot. A heavy outcome of a ulcer of feet is amputation of the lower extremity, which at patients with DM is carried out 10-30 times more often in comparison with all population. The remote lethality at patients with critical ischemia of the lower extremity (CILE) at DM in the first year about 20% and in five years of 40% - 70%. The carried-out analyses of the latest literary data to us allowed to draw the following conclusions: 1. DFS remains an urgent problem of surgery at which to 85% disability occurs, about 20-30% the lethality rates. 2. At diagnosis of DFS more the electroneuromyography, a X-ray contrast angiography, a transdermal polyarography and MRT affected extremities efficiently. 3. Early diagnosis of a disease and correction of complications with prevention of critical ischemia of the lower extremity promotes an reduction of terrible complications, such as gangrene of the lower extremity which comes to the end with amputation of an extremity. 4. The combined defeat of small and large vessels occurs at most of patients with a diabetes mellitus that is the reason not of efficiency of treatment using stenting and surgical intervention of arteries of the lower extremity. 5. Classification of DFS by Wagner (1981) is more optimal for practical surgery.